A Mixed Methods Study of Organizational Readiness for Change and Leadership during a Training Initiative within Community Mental Health Clinics - Stanhope, Victoria (Adm Policy Ment Health, 2019)
This longitudinal mixed-methods study explored variation in organizational readiness for change and leadership behavior across seven organizations during a 12-month training initiative in person-centered care planning. Quantitative data was used to examine trajectories of organizational readiness for change and leadership behavior over time and qualitative data explored provider perspectives on the trajectory of these organizational factors during the 12-month training initiative. Findings indicated that levels of organizational readiness for change and leadership behavior varied across clinics, but most experienced a significant positive change at the mid-point of the training. Organizational readiness for change was positively correlated with leaderships behaviors across time. Provider focus group findings gave insight into their initial resistance to adopting the new practice and their increasing receptivity in the second six months due to increased understanding of the practice and leadership endorsement. Increasing provider openness to a new practice prior to training and having a consistently engaged leadership have the potential to improve the efficiency of a training initiative.